Using Metabolic Engineering to Connect Molecular Biology Techniques to Societal Challenges - Gordy, Claire L.; Goller, Carlos C. (Frontiers in Microbiology, 2020)
Genetically modified organisms (GMOs) are a topic of broad interest and are discussed in classes ranging from introductory biology to bioethics to more advanced methods-focused molecular biology courses. In most cases, GMOs are discussed in the context of introducing a single protein-coding gene to produce a single desired trait in a crop. For example, a commercially available kit allows students to test whether food products contain GMOs by detecting the Bacillus thuringiensis delta-endotoxin gene, which confers resistance to European corn borers. We have developed an 8-week laboratory module for upper-division undergraduates and graduate students that builds upon students’ basic understanding of GMOs to introduce them to the techniques used to sustainably produce commercially valuable products in yeast through metabolic engineering. In this course, students use recombination-based methods to assemble genes encoding entire metabolic pathways in Saccharomyces cerevisiae, perform genetic screens to identify yeast genes that impact metabolite yield, and use error-prone PCR to optimize metabolic pathway function. In parallel to these laboratory-based activities, students engage with the societal impact of these approaches through case studies of products made via yeast metabolic engineering, such as opioids, omega-3 fatty acids, and the Impossible Burger. In this report, we focus on these case studies as well as an individual sustainability project assignment created for this course. This assignment, which spans the 8-week module, asks students to find examples of yeast metabolic engineering that could be used to address current sustainability challenges in their communities. By the end of the course, students synthesize this information to create a case study that could be used to teach concepts related to metabolic engineering and sustainability to their peers. Student approaches to this project have varied from literature reviews, to news searches, to directly contacting and interviewing researchers using novel metabolic engineering approaches. These student-produced projects are used as case studies in future semesters, amplifying student voices and contributing to student ownership. While developed in the context of this course, the sustainability project and case studies are broadly applicable and could be adapted for use in biology or bioethics courses at the undergraduate or graduate level. Through this report, we hope to gain collaborators interested in implementing a version of the course at their institutions, allowing for robust assessment of the impact of the course on a larger group of students.